Aktivitas Antioksidan serta Penghambatan HMG CoA dan Lipase dari Kombinasi Ekstrak Daun Binahong-Rimpang Temu Lawak - Yunarto, Nanang; Aini, Nurul; Oktoberia, Intan Sari; Sulistyowati, Indah; Kurniatri, Arifayu Addiena (Jurnal Kefarmasian Indonesia, 2019)
TThe prevalence of dyslipidemia in Indonesia continues to increase. Anredera cordifolia and Curcuma xanthorrhiza are empirically used in the community to overcome dyslipidemia disorders. Flavonoids as the main compounds in A. cordifolia and curcumin in C. xanthorrhiza have potential as antioxidant activity. This study aims to determine the in vitro mechanism of A. cordifolia and C. xanthorrhiza to reduce cholesterol associated with antioxidant activity. The testing was carried out on a combination of ethanol extracts of A. cordifolia leaves with C. xanthorrhiza rhizomes (1:1) and their single extract. The antioxidant activity test was conducted using DPPH method by making serial dilution of samples and ascorbic acid with adding DPPH. The inhibitory activity of HMG CoA and lipase enzymes was carried out enzymatically using ELISA as well as simvastatin as the comparison. The results showed that the highest antioxidant activity is in C. xanthorrhiza extract samples IC50 16.21 ± 1.74 µg/mL, but was less potential compared to ascorbic acid IC50 7,63±0,85 µg/mL. The most potential inhibition of HMG CoA and lipase is in C. xanthorrhiza samples IC50 8.35 ± 0.02 and 22.35 ± 1.26 µg/mL. The combination of A. cordifolia and C. xanthorrhiza (1: 1) is better than A. cordifolia extract but lower than C. xanthorrhiza extract in antioxidant activity as well as the inhibition of HMG CoA reductase and lipase. The result showed a correlation that the higher antioxidant activity, the higher inhibitory of HMG CoA reductase and lipase respectively.